2024
DOI: 10.1002/adma.202311515
|View full text |Cite
|
Sign up to set email alerts
|

NIR‐II Protein‐Escaping Dyes Enable High‐Contrast and Long‐Term Prognosis Evaluation of Flap Transplantation

Yijing Du,
Jiajun Xu,
Xue Zheng
et al.

Abstract: Real‐time vascular positioning, postoperative flap monitoring, and vascular reconstruction assessment are of great importance in flap transplantation. Cyanine dyes offer the advantage of high resolution in the Near‐infrared‐II (NIR‐II) imaging window. However, the nonspecific binding of many cyanine dyes to endogenous albumin leads to high organ accumulation and skin absorption, resulting in low‐quality imaging and poor reproducibility of contrast during long‐term (e.g., 7 days) postoperative monitoring. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…The results revealed that the fluorescence intensity of the nerve decreased over time after 78% ZrNPs injection, with no detectable signals within 24 h. This allowed for three independent neuroimaging sessions which didn't interfere with each other (Figure 4b). We further designed and synthesized an albumin-escaping dye, IR-808Ac, [49] aiming to prevent covalent binding to albumin and facilitating quick excretion from the body after intravenous injection, resulting in low imaging background signal (Figure S22a,b, Supporting Information). Besides, IR-808Ac and 78% ZrNPs could be separately excited by 808 and 980 nm lasers, without any fluorescent crosstalk, which was the basic of dual-channel imaging (Figure 4c,d and Figure S22c, Supporting Information).…”
Section: Multiple Neuroimaging and Dual-channel Fluorescence Imaging ...mentioning
confidence: 99%
“…The results revealed that the fluorescence intensity of the nerve decreased over time after 78% ZrNPs injection, with no detectable signals within 24 h. This allowed for three independent neuroimaging sessions which didn't interfere with each other (Figure 4b). We further designed and synthesized an albumin-escaping dye, IR-808Ac, [49] aiming to prevent covalent binding to albumin and facilitating quick excretion from the body after intravenous injection, resulting in low imaging background signal (Figure S22a,b, Supporting Information). Besides, IR-808Ac and 78% ZrNPs could be separately excited by 808 and 980 nm lasers, without any fluorescent crosstalk, which was the basic of dual-channel imaging (Figure 4c,d and Figure S22c, Supporting Information).…”
Section: Multiple Neuroimaging and Dual-channel Fluorescence Imaging ...mentioning
confidence: 99%